Successful E-Commerce in A Week - Howell, Dave (London Hodder & Stoughton, 1999)
This work provides practical advice to enable any business to enter into the rapidly expanding marketplace. It covers: payment methods; suitable systems; ensuring the company web site is secure; methods for delivering goods; legal issues; and how to put into effect a plan for trading online.
Includes Illustrations
Institute of Management
Keywords: Electronic commerce